1975
DOI: 10.1007/bf02672168
|View full text |Cite
|
Sign up to set email alerts
|

Sampling cottonseed lots for aflatoxin contamination

Abstract: Large samples called “sublots” were drawn from 41 commercial lots of contaminated cottonseed. Each sublot was subdivided into twenty 5 lb samples which were analyzed for aflatoxin. The mean, median, variance, coefficient of variation, and the estimated range among the sample concentrations were computed. The results indicated that: (A) the variance among sample concentrations was large and was found to be a function of sample concentration and (B) the distribution of sample concentrations was skewed; the densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Sampling variance accounts for the majority of the total variance, followed by sample preparation and analytical variance. This is consistent with what has been observed with other mycotoxins and other commodities ( Johansson et al 2000b;FAO 1993;Velasco et al 1975;Whitaker et al 1976Whitaker et al , 1994aWhitaker et al , 2000Whitaker et al , 1998Whitaker et al , 1974). For small sample sizes, sampling is usually the largest source of error.…”
Section: Total Variancesupporting
confidence: 91%
See 1 more Smart Citation
“…Sampling variance accounts for the majority of the total variance, followed by sample preparation and analytical variance. This is consistent with what has been observed with other mycotoxins and other commodities ( Johansson et al 2000b;FAO 1993;Velasco et al 1975;Whitaker et al 1976Whitaker et al , 1994aWhitaker et al , 2000Whitaker et al , 1998Whitaker et al , 1974). For small sample sizes, sampling is usually the largest source of error.…”
Section: Total Variancesupporting
confidence: 91%
“…Although methods have been developed to evaluate and design sampling plans for aflatoxins ( Johansson et al 2000b;FAO 1993;Velasco et al 1975;Whitaker et al 1976Whitaker et al , 1994aCODEX 2001), deoxynivalenol (Whitaker et al 2000), and fumonisins , none of them were designed for OTA in coffee. The objectives of this study were:…”
Section: Introductionmentioning
confidence: 98%
“…Three distributions may be used to describe the variability of test results ~ about the lot concentration p: (a) distribution of sample concentrations xs about the lot concentration p, (b) distribution of subsample concentration Xss about the sample concentration Ps, and (c) distribution of analytical determinations Xa about the subsample concentration Pss. Previous studies on peanuts and cottonseed (1,2,5) have indicated that the sample and subsample distributions can be simulated best with a skewed-type probability distribution function, whereas the analytical distribution tends to be more nearly normal.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The concentration of aflatoxin in cottonseed lots is estimated by analyzing samples taken from each lot. The estimations are difficult to make because of the large variability associated with replicated test results on the contaminated lot (1,2). Typical steps taken to estimate the aflatoxin concentration in cottonseed lots are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, dry and slurry grinding have been investigated to accurately estimate mycotoxin levels in various matrices using different types of mills (Dickens and Satterwhite 1969;Whitaker et al 1974Whitaker et al , 1980Velasco and Whitaker 1975;Velasco and Morris 1976;Dorner and Cole 1993;Calori-Dominges et al 2000).…”
Section: Introductionmentioning
confidence: 98%